The Roman policy in the exploitation of the chemtou marbles quarries - Bakhadra, Abdul Qader (The Algerian Historical Journal, 2026)
The topic discusses the Chemtou marble quarries during the Roman period, providing a descriptive overview of the quarries and the early stages of their exploitation. It highlights the quality of the marble extracted, the development of the Roman exploitation system, and the organization of transportation and export. It also touches on the main challenges that accompanied the exploitation of these quarries. he topic also examines the nature of Roman management of the Chemtou quarries and the workforce employed in quarry operations. It describes the working methods used to extract marble, focusing on the significance of the quarries, the resources the Romans allocated to operate them, and their overall scale and dimensions.